An ultra-wide bandwidth (704 to 4 032 MHz) receiver for the Parkes radio telescope. (2020) - Hobbs, George; Manchester, Richard N.; Dunning, Alex; Jameson, Andrew; Roberts, Paul; George, Daniel; Green, J. A.; Tuthill, John; Toomey, Lawrence; Kaczmarek, Jane F.; Mader, Stacy; Marquarding, Malte; et al.
Abstract: We describe an ultra-wide-bandwidth, low-frequency receiver recently installed on the Parkes radio telescope. The receiver system provides continuous frequency coverage from 704 to 4032 MHz. For much of the band ( ${\sim}60%$ ), the system temperature is approximately 22 K and the receiver system remains in a linear regime even in the presence of strong mobile phone transmissions. We discuss the scientific and technical aspects of the new receiver, including its astronomical objectives, as well as the feed, receiver, digitiser, and signal processor design. We describe the pipeline routines that form the archive-ready data products and how those data files can be accessed from the archives. The system performance is quantified, including the system noise and linearity, beam shape, antenna efficiency, polarisation calibration, and timing stability.